The effectiveness of using the Spelling Bee method to improve Arabic vocabulary comprehension among Junior High School Students of Dar El-Hikmah Pekanbaru/ Fa’ãliyatu Istikhdãmi TarÎqah Spelling Be Litarqiyati Isti’ãb al-Mufradãt al-Arabiyah lada Thullãbi fi al-Madrasah al-Mutawassithah bi Ma’hadi Dãr al-Hikmah Pekanbaru - Prabangestha, Prabangestha; Kasmiati, Kasmiati; Masbukin, Masbukin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
ملخّصيستخدم هذا البحث مقاربة كميا مع تصميم البحث التجربي، يتكون من متغيرين وهما طريقة